A gestão dos vestígios arqueológicos da Batalha de Aljubarrota nas práticas discursivas salazaristas - Gomes, Sérgio Alexandre (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2017)
In this article I will discuss how the archaeological evidence of the Battle of Aljubarrota was managed by Salazarism’s politics of memory. The archaeology was discovered by Afonso do Paço at the end of the 1950s, and he subsequently interpreted it according to the regime’s point of view of the historical episode. Considering the importance of the site, Paço suggested its preservation and also for it to be presented to a wider public in order to commemorate the memory of the battle. However, the project was rejected and the archaeological remains were put aside from the commemorations. In terms of Salazarism’s discourse practices, I aim to contribute a better understanding of how these new elements related to the battle were overlooked in favor of a former ritual to celebrate Aljubarrota.